Mucocele associated with an ectopic tooth in the maxillary sinus: A case report - Kaygusuz, Irfan; Karlidag, Turgut; Akyigit, Abdulvahap; Yalcin, Sinasi (Elsevier Ireland Ltd, 2011)
Ectopic tooth are rarely found in the maxillary sinus. In rare cases, occlusion of the sinus ostia may predispose a patient to develop a maxillary sinus mucocele. Extraction of the tooth with excision of mucocele resulted in relieving of the symptoms. Here, we present a case of mucocele with an ectopic maxillary tooth located in medial antral wall, over the ostium area in a nine-year-old girl. We evaluated the clinical features, etiologic factors, challenging properties, signs and symptoms of the ectopic tooth in the maxillary sinus. (C) 2011 Elsevier Ireland Ltd. All rights reserved.
Keywords: Ectopic tooth; Mucocele; Maxillary sinus